Boosting children's math self-efficacy by enriching their growth mindsets and gender-fair beliefs. Issue 1 (2nd January 2022) - Lee, Jeesoo; Lee, Hyun Ji; Bong, Mimi
ABSTRACT: Self-efficacy is easily the most important construct for engagement and success in achievement contexts. In this article, we aim to promote a better understanding of theory-driven practices that foster students' self-efficacy beliefs in math, especially the practices that change young learners' mindset and gender stereotypes in math. We briefly present the self-efficacy theory first, followed by theoretical and empirical findings within the mindset and stereotype literature that are relevant to self-efficacy enhancement. Next, we introduce the core concepts and messages, embedded psychological processes, and unique design features of a recent math intervention delivered as part of regular classroom instruction, which has proven effective for enriching children's growth mindsets and gender-fair beliefs regarding math ability.